Quadratic Formula
x = - b ± √b² - 4ac / 2a
x² - 2x + 1
a = 1
b = - 2
c = 1
x = - (- 2) ± √(- 2)² - 4(1)(1) / 2(1)
x = 2 ± √4 - 4 / 2
x = 2 ± 0 / 2
x = 2 / 2
x = 1
- - - - - - -s-
2007-04-05 08:09:13
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
Ok you know the quadratic formula.
-(b) [+or-] sqrt(b^2-(4)(a)c)
x {the variable you are solving for}= ------------------------------------
2(a)
now you have your equation x^2-2x+1=0 {have equation set to zero so you can use the formula}
I like to use a little trick to get rid of the 2 in front of the a on the bottom. Thus you get your a now=a/2,b now =b/2, and c now =c/2.You times your whole equation by (1/2) so then whatever your a is you get 2(a/2).
In your equation your a (with the trick would be) (1/2) because you have only a one in front of your x^2. Then your b would be (-2)/2 {have -2 from the minus 2x}, and your c would be (1/2). Now just plug in those values where you see the corisponding letter in the equation above.
2007-04-05 07:42:17
·
answer #2
·
answered by Michael M 4
·
0⤊
0⤋
x^2-2x+1=0
x = {2 +/- sqrt(4-4)}/2
x = 2/2 = 1
1 is a double root of the given equation.
2007-04-05 07:29:04
·
answer #3
·
answered by ironduke8159 7
·
0⤊
0⤋
a million] sqrt2x^2 -x - sqrt2 = 0 x = [a million +/- sqrt[a million + 4*2]]/2sqrt2 x = [a million +/- sqrt 9]]/2sqrt2 x = 2/sqrt2 or -a million/sqrt2 so factors are [x - sqrt2][x + a million/sqrt2] 2] sqrt2x^2 + x - 10sqrt2 x = [-a million +/-sqrt [a million + 80]]/2sqrt2 x = [-a million +/- 9]/2sqrt2 x = -5/sqrt2 or 4/sqrt2 x = -3.fifty 4 or 2.80 3 factors are [x + 3.fifty 4][x - 2.80 3] = 0 have left one in root style and the different in decimal you could decide for
2016-10-21 02:53:29
·
answer #4
·
answered by Erika 4
·
0⤊
0⤋
a=1, b=-2, c=1. Plug them in the formula.
2007-04-05 07:30:46
·
answer #5
·
answered by fredoniahead 2
·
0⤊
0⤋
Another way to do these is:
x^2 + bx + c = 0
Find two numbers, d and e, such that d+e=b and d*e=c. Then these goes into the equation:
(x+d)(x+e)=0
In this case, -1 -1 = -2 and (-1)(-1) =1
(x-1)(x-1)=0
x=1 (m2)
2007-04-05 07:33:47
·
answer #6
·
answered by kefkakrist 2
·
0⤊
0⤋
x1,2 = [2 +- sqrt((-2)^2 - 4*1*1)]/2 = [2 +- sqrt(4 - 4)]/2 = 2/2 = 1
2007-04-05 07:28:27
·
answer #7
·
answered by Amit Y 5
·
0⤊
0⤋
x = {-(-2) +- sqr[(-2)^2 - 4(1)(1)]}/2(1)
= {2 +- sqr[4 - 4]}/2 = 1 for both roots
2007-04-05 07:31:24
·
answer #8
·
answered by kellenraid 6
·
0⤊
0⤋